Application and analysis of just in time teaching methods in a calculus course - Natarajan, Rekha (Kansas State University, 2012)
"Just In Time Teaching" (JiTT) is a teaching practice that utilizes web based technology to collect information about students' background knowledge prior to attending lecture. Traditionally, students answer either multiple choice, short answer, or brief essay questions outside of class; based on student responses, instructors adjust their lectures "just-in-time." In this study, modified JiTT techniques in the form of online review modules were applied to a first semester calculus course at a large midwestern state university during the spring 2012 term. The review modules covered algebra concepts and skills relevant to the new material presented in calculus lecture (the "just-in-time" adjustment of the calculus lectures was not implemented in this teaching experiment). The reviews were part of the course grade. Instead of being administered purely "just-in-time," the reviews were assigned ahead of time as part of the online homework component of Calculus-I. While previous studies have investigated the use of traditional JiTT techniques in math courses and reported student satisfaction with such teaching tools, these studies have not addressed gains in student achievement with respect to specific calculus topics. The goal of this study was to investigate the latter, and to determine whether timing of the reviews plays a role in bettering student performance. Student progress on weekly Calculus-I online assignments was tracked in spring of 2012 and compared to student scores from weekly Calculus-I online assignments from spring 2011, when modified JiTT instruction was not available. For select Calculus-I online assignments during the spring 2012 term, we discovered that the review modules significantly increased the number of students receiving perfect scores, even when the reviews were not purely administered ``just-in-time." Analysis of performance, success of review assignments, and future implications are also discussed.
Keywords: Just in time teaching calculus; Mathematics Education (0280)